DÖNEMEÇTE ROMANINA EDEBİYAT SOSYOLOJİSİ AÇISINDAN BİR BAKIŞ. - ÇAKIR, Dilek (Marmara University Journal of Turkology / Marmara Türkiyat Araştırmaları Dergisi)
Tarık Buğra's Dönemeçte novel is one of the most appropriate to examine is terms of literature sociology. This piece is a period novel which is described in background of Tarık Buğra's love affoir between Doctor Şerif, Handan and Orhan and this piece is about Tarık Buğra's passage period negative or positive silvations, this prossesing's outlook and impression over public and endightened people. In the novel, many problems, which is about period's public history, are mantioned from canflict between public and anlighttened people to devoloping process of Democrat batch, from İsmet İnönü who is chararterized Public (Halk) batch and nationel general to changing of standpaint thanks to foundation of Democrat batch and wealthy public thanks to increase in cost of grain, swang the money being not know how it should use; in terms of these that piece is very appropriate to read sociological. Almost that piece worths a secret treasure which mentions to social events. These two groups who are calls public and enlightened people are seen is shope of passage to multiple batch between 1946 and 1948 this process's progress and different impressions on public and enlightened people are montioned at large giving examples ovet public and enlightened people's conflicts. In the period of Democrat batch is getting wealthy, in the work, education, relation between men and women, segregation between public and enlightened people were handled at large.